2017
DOI: 10.1186/s12909-017-0862-y
|View full text |Cite
|
Sign up to set email alerts
|

Two birds with one stone: experiences of combining clinical and research training in addiction medicine

Abstract: BackgroundDespite a large evidence-base upon which to base clinical practice, most health systems have not combined the training of healthcare providers in addiction medicine and research. As such, addiction care is often lacking, or not based on evidence or best practices. We undertook a qualitative study to assess the experiences of physicians who completed a clinician-scientist training programme in addiction medicine within a hospital setting.MethodsWe interviewed physicians from the St. Paul’s Hospital Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Ministry of Health. For further description of how the programme is delivered, please refer to previous publication [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ministry of Health. For further description of how the programme is delivered, please refer to previous publication [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Developing research capacity among ECAMPs from low and lower-middle-income countries by conducting workshops with the support of facilitators from high-income countries can be a solution for the problem. Other allied addiction medicine professionals can also be engaged in such training programmes to develop workforce and build more capacity (35, 38, 39). The main challenges encountered for conducting research by ECAMPs in the European survey (n=258) were lack of time as a large proportion of participants (87.2%) reported conducting research after regular working hours or partly during and after working hours.…”
Section: Discussionmentioning
confidence: 99%
“…Both the quantitative and qualitative phases of this study highlighted the influence of confidence and value on motivation to do research and undertake research training. [57][58][59][60] The study findings showed that participants who had prior research training were more confident than those who had not been previously exposed to training. Previous research training was viewed positively by respondents and significantly influenced their expectations about participating in research.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%